The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/14992027.2017.1366078
|View full text |Cite
|
Sign up to set email alerts
|

Development of a method for determining binaural sensitivity to temporal fine structure

Abstract: Objective: To develop and evaluate a test of the ability to process binaural temporal-fine-structure (TFS) information. The test was intended to provide a graded measure of TFS sensitivity for all listeners. Design: Sensitivity to TFS was assessed at a sensation level of 30 dB using the established TFS-LF test at centre frequencies of 250, 500 and 750 Hz, and using the new TFS-AF test, in which the interaural phase difference (IPD) was fixed and the frequency was adaptively varied. IPDs varied from 30 to 180. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 50 publications
(91 reference statements)
5
70
0
Order By: Relevance
“…Young NH listeners can detect changes in IPD for sinusoids with frequencies up to about 1,400 Hz [86]. However, the upper frequency limit varies considerably across individuals [87]. It is not known whether the individual differences reflect differences in the neural coding of binaural TFS information or differences in auditory processing efficiency (the ability to make use of a limited amount of sensory information).…”
Section: Binaural Processing For Normal-hearing Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Young NH listeners can detect changes in IPD for sinusoids with frequencies up to about 1,400 Hz [86]. However, the upper frequency limit varies considerably across individuals [87]. It is not known whether the individual differences reflect differences in the neural coding of binaural TFS information or differences in auditory processing efficiency (the ability to make use of a limited amount of sensory information).…”
Section: Binaural Processing For Normal-hearing Subjectsmentioning
confidence: 99%
“…Some older subjects are completely unable to perform the TFS-LF test, and hence no graded measure of sensitivity to TFS is obtained. Füllgrabe et al [87] modified the TFS-LF test to overcome this limitation. In their test, referred to as the TFS-AF test (where AF stands for adaptive frequency), the IPD is fixed, usually at 180 , and the frequency of the tone is adaptively varied, as was done in some of the studies described earlier [137].…”
Section: Effects Of Age and Hearing Lossmentioning
confidence: 99%
“…The initial value of ϕ is usually set to 180°, and ϕ is adaptively varied to determine the threshold. Although this test has frequently been used to assess sensitivity to binaural TFS ( Ernst & Moore, 2012 ; Füllgrabe, 2013 ; Füllgrabe et al., 2015 ; Füllgrabe, Harland, Sęk, & Moore, 2017 ; Hopkins & Moore, 2011 ; Léger, Moore, & Lorenzi, 2012 ; Lőcsei et al., 2016 ; Moore, Glasberg, Stoev, Füllgrabe, & Hopkins, 2012a ; Moore, Vickers, & Mehta, 2012b ; Neher et al., 2012 ; Oberfeld & Klöckner-Nowotny, 2016 ; Perez et al., 2014 ; Rönnberg et al., 2016 ; Sharma, Dhamani, Leung, & Carlile, 2014 ; Whitmer, Seeber, & Akeroyd, 2014 ), it has been repeatedly observed that some listeners are unable to perform the task, and hence no graded measure of sensitivity to TFS is obtained for those listeners.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of experiments with YNH listeners (with audiometric thresholds ≤ 20 dB hearing level [HL] from 125 to 8000 Hz), Füllgrabe et al. (2017) established that all listeners were able to perform the TFS-AF test reliably, there was no trend for performance to improve with practice, and thresholds were strongly negatively correlated with those measured using the TFS-LF test (high frequencies at threshold for the TFS-AF test are associated with good TFS sensitivity, which in turn is associated with low thresholds in degrees for the TFS-LF test).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency starts at a low value, such as 200 Hz. Most subjects can perform the task well when the frequency is low, but performance worsens when the frequency increases, and above some frequency the task becomes impossible [57,58]. Hence, the highest frequency at which the task can be performed gives a measure of binaural sensitivity to TFS.…”
Section: Sensitivity To Temporal Fine Structure (Tfs)mentioning
confidence: 99%